2004
DOI: 10.1115/1.1625396
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of an Industrial Aluminum Melting Furnace

Abstract: For the present work, a numerical simulation of the 100% oxy-firing combustion process inside an industrial aluminum remelting reverb furnace is presented. Three different configurations were analyzed: (i) a staged combustion process with parallel injection jets for oxygen and natural gas, (ii) a staged combustion process with a divergent jet for the oxygen, and (iii) a non-staged combustion process, with parallel jets. In all the cases, the injections were directed towards the aluminum bath, which was maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The analysis of transient heating characteristics of the steel in an industrial furnace has attracted considerable attention during the past few decades especially when such processes should have lower energy consumption and pollutant emissions [1,2]. In addition, requirement of a uniform temperature distribution inside the volume for the treated workpieces is of great importance to determine the quality of the steel product in terms of hardness, toughness and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of transient heating characteristics of the steel in an industrial furnace has attracted considerable attention during the past few decades especially when such processes should have lower energy consumption and pollutant emissions [1,2]. In addition, requirement of a uniform temperature distribution inside the volume for the treated workpieces is of great importance to determine the quality of the steel product in terms of hardness, toughness and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of transient heating characteristics of the steel in an industrial furnace has attracted considerable attention during the past few decades especially when such processes should have lower pollutant emissions and energy consumption [18,22,26]. Recall that an uniform temperature distribution inside the industrial furnaces is of great importance for the treated workpieces in order to determine their quality in terms of hardness, toughness and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, experimental tests demonstrated that the furnace performance could be improved significantly by optimization of operation parameters [2]. ZIMONT et al [3] developed a computer model to simulate the turbulent combustion of premixed gases in an aluminum holding furnace.…”
Section: Introductionmentioning
confidence: 99%